Determination of the Level of PCBs in Small Fishes from Three Different Coastal Areas of Karachi, Pakistan - Munshi, A. B.; Hina, A. S.; Usmani, T. H. (Biological Sciences - PJSIR, 2005)
The level of congener polychlorinated biphenyls (PCBs) was determined in small fishes. These fishes were collected from the beaches of Korangi Creek, Hawksbay and Clifton, all located in Karachi, Pakistan. The contamination status of PCBs was followed by their concentration in tissues. Higher PCBs were found to be the most persistent organopllutants, present in all the fishes studied.The samples were spiked with 5µl surrogate internal standard solution containing IUPAC numbers 194 and 198. A total of 14 PCBs were screened in each sample. The concentrations of PCBs found were 1.25 ± 0.02 ng/g dry weight of fishes collected from Clifton, 1.01 ± 0.52 ng/g of fishes collected from Hawksbay, and 1.00 ± 0.43 ng/g of fishes collected from Korangi Creek. The congener PCBs 138,153, and in some small fishes 118, were found to be predominant among all the PCBs tested in this study.